Pedagogic moments: adventures in relatedness, touch and tact - Nicholson, Victoria Stella (Curtin University, 2015)
This thesis is an interpretive inquiry that seeks hermeneutic understandings of pedagogic moments through encountering and interrogating my lifeworld. I question our understanding of mind, self, other, world, and reality that informs our worldview. My inquiry manifests evidence that pedagogy is something we are and can be rather than something we do. It is a tribute to pedagogy’s ineffability, found in relating, touch and tact, showing pedagogy as a desirable phenomenon for human science research.